“Diseño de un plan de mejoramiento integral para la comisión de divisiones formativas de liga deportiva Universitaria, ubicado en la ciudad de Quito” - Arboleda Rojas, Juan Carlos (2013)
The development of this thesis consists of a comprehensive improvement plan for the Committee on Formative Divisions Liga Deportiva Universitaria Quito, which is dedicated to training players to come to first class and represent our country in national and international games , it will further specify the main problem is the commission of formative divisions. It will conduct an analysis of the history of Liga and its organizational culture The club itself was founded in 1930, with the passing of the years LDU Quito was the need to have its own pool of players in order to train them from childhood in the technical, physical, and academic and thus have a greater chance of reaching first category as good players so we can get a win for either team players transferring internationally or nationally and make a profit for club coffers.